Perencanaan Rute Aman Selamat Sekolah (RASS) bagi Pesepeda di Pekanbaru - Dian P. S. Salmiati; Mimi Arifin; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
The increase in bicycle users during the pandemic by school age in Pekanbaru increased quite significantly, this has become the basis for planning the implementation of Safe Routes to School (SRTS) for cyclists. This planning was carried out to follow up on the Minister of Transportation Regulation No. PM 16 of 2016 as an effort to increase the use of bicycles to school by providing infrastructure that provides safe and secure rights for its users. This research was conducted with the aim of providing directions for Safe and SRTS for cyclists in Pekanbaru. Secondary data collection is in the form of a literature study by examining the factors that influence determining safe and safe bicycle routes to school and reviewing SRTS planning guidelines for cyclists. Primary data was obtained from observations and documentation to identify the existing condition of the factors that influence route determination on the case study roads. This research was conducted from March to August 2021, located in Pekanbaru. The analysis used is a systematic review, quantitative, spatial, descriptive qualitative, and MKJI. Based on the results of the Systematic Review, several dominant variables influence the determination of safe and safe bicycle routes to school, namely traffic volume, traffic speed, points of conflict/intersection and physical condition of the road. with the RASS recommendation directives for cyclists in Pekanbaru City located on Jl. General Soedirman - Jl. Kaharuddin Nst – Jl. Soekarno-Hatta – Jl. Arifin Ahmad – Jl. HR. Soebrantas – Jl. Riau – Jl. Yos Soedarso – Jl. Pope – Jl. nineg.